2014
DOI: 10.1002/2014rg000450
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy assessment of global barotropic ocean tide models

Abstract: The accuracy of state-of-the-art global barotropic tide models is assessed using bottom pressure data, coastal tide gauges, satellite altimetry, various geodetic data on Antarctic ice shelves, and independent tracked satellite orbit perturbations. Tide models under review include empirical, purely hydrodynamic ("forward"), and assimilative dynamical, i.e., constrained by observations. Ten dominant tidal constituents in the diurnal, semidiurnal, and quarter-diurnal bands are considered. Since the last major mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
373
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 404 publications
(406 citation statements)
references
References 107 publications
10
373
3
Order By: Relevance
“…It has been shown that the surface signature of internal tide, evaluated by sea surface satellite products, is reasonably well captured. The barotropictide-induced sea level variability is captured to 93 % and a recent barotropic tide model intercomparison shows that STORMTIDE ranks similar to other modern hydrodynamic tide models (Stammer et al, 2014).…”
Section: Numerical Modellingmentioning
confidence: 72%
“…It has been shown that the surface signature of internal tide, evaluated by sea surface satellite products, is reasonably well captured. The barotropictide-induced sea level variability is captured to 93 % and a recent barotropic tide model intercomparison shows that STORMTIDE ranks similar to other modern hydrodynamic tide models (Stammer et al, 2014).…”
Section: Numerical Modellingmentioning
confidence: 72%
“…The grid resolutions of these models vary from 1/30° to 1/2°. Different from Stammer et al (2014), OSU12 model is not adopted in our study, since it has not yet covered the polar oceans and defaults to GOT4.8 at high latitudes (Fok 2012). FES2004 is taken as the representative model of classical and conventional models, to validate the accuracy improvement of state-of-the-art models in Antarctica.…”
Section: Tide Modelsmentioning
confidence: 99%
“…Where k is the index of grid point, P is the number of all grid wet points. The studying regions of this paper are oceans southward of 30°S, in order to show the real discrepancy between models, the down-weighted strategy of Stammer et al (2014) was not adopted, instead, we use evenly weighted strategy. The results are separately listed in the table 2 for the Ice Shelf regions (including regions of permanent sea ice), the shallow seas (depth < 1000 m) and the deep ocean (depth > 1000 m), respectively.…”
Section: Tpxo8mentioning
confidence: 99%
See 1 more Smart Citation
“…It participates in the ocean tides with substantial modulation of the tidal signal compared to the nearby Atlantic Ocean [5]. Satellite altimetry is the principal data source for recent global ocean tide models [6]; but its applicability over the narrow Río de la Plata is very limited because standard procedures do not provide reliable sea-surface heights in coastal waters [7]. [8] derived a regional tide model for the estuary from tide gauge records at 34 sites.…”
Section: Introductionmentioning
confidence: 99%